Self-Immolative Polymersomes for High-Efficiency Triggered Release and Programmed Enzymatic Reactions - Liu, Guhuan; Wang, Xiaorui; Hu, Jinming; Zhang, Guoying; Liu, Shiyong (Journal of the American Chemical Society, 2014)
Stimuli-triggered disassembly of block copolymer vesicles or polymersomes has been conventionally achieved via solubility switching of the bilayer-forming block, requiring cooperative changes of most of the repeating units. Herein we report an alternative approach by incorporating hydrophobic blocks exhibiting stimuli-triggered head-to-tail cascade depolymerization features. Amphiphilic block copolymers bearing this motif self-assemble into self-immolative polymersomes (SIPsomes). By modular design of terminal capping moieties, visible light, UV light, and reductive milieu can be utilized to actuate SIPsomes disintegration into water-soluble small molecules and hydrophilic blocks. The design of SIPsomes allows for triggered drug co-release and controllable access toward protons, oxygen, and enzymatic substrates. We also demonstrate programmed (OR-, AND-, and XOR-type logic) enzymatic reactions by integrating SIPsome encapsulation and trigger/capping moiety-selective cascade depolymerization events.